Efek Sinergis Vitamin C Dalam Meningkatkan Kinerja Antijamur Madu Apis dorsata Terhadap Biofilm Candida albicans Untuk Terapi Kandidiasis - MASFUFATUN; ZAHRA, FATIMATUZ; AGUSTIN ANGRAENI, DWI PUTRI; NUZULA, FIRDAUSI (Hang Tuah Medical Journal, 2024)
Honey is a natural ingredient produced by bees from flower nectar that has antimicrobial, antioxidant, anti-inflammatory, good wound healing effects, and bacteriostatic. This study aims to determine the synergistic effect of vitamin C in improving the antifungal performance of Apis dorsata honey against Candida albicans biofilm for candidiasis therapy. This research design is true experimental with a post-test only control group design approach using the microtiter plate assay method to measure the Optical Density (OD) value of the biofilm matrix. The test of the synergistic effect of Vitamin C on Honey was carried out by adding vitamin C to honey concentrations of 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, and 50%. Furthermore, the MBIC50 value between honey and the combination of honey and vitamin C was compared. The results showed that both honey and the combination of honey and vitamin C were each able to decrease the growth of C. albicans biofilm matrix against A. dorsata honey at various concentrations. The results of the Minimum Biofilm Inhibitory Concentration 50% (MBIC50) value in A. dorsata honey and the combination of A. dorsata honey and vitamin C were 84.27% and 63.56% respectively. Based on this study, it can be concluded that vitamin C can increase the antifungal performance of A. dorsata by lowering the MBIC50 value. Thus, the combination of vitamin C and honey can be used as an alternative therapy for candidiasis.